Democracy and Feudalistic between Daisy Miller and Mrs. Costello through Sociological Approach as reflected in Daisy Miller (1879) - Edi Ardian (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2019)
There are several kinds of literary works. They are a poem, novel, fiction, drama,etc. Daisy Miller is one of the famous and popular novels. This novel is written inthe spring of London. The Author is Henry James. The writer analyzed this novel bythe sociological approach. This research applies qualitative research which thedata are taken from the analysis document and material from books and internetresearch. Data analysis concerns the interpretative technique that focuses onexamining data. The main source of this research is the novel Daisy Miller thisresearch is going to answer the research questions what is the characteristic ofdemocracy and Feudalistic is as reflected in Daisy miller novel? And what are thephenomena between democracy and Feudalistic in Daisy Miller novel? From theanalysis the author concluded that Daisy Miller is a representative of Americanwoman as same as democracy in the American Custom, She is going abroad toSwitzerland which is peaceful country inhabited by all kinds of people of differentrace, ethnic, language, skin color, religion, profession, from all over the world.The Henry James as the author showed Daisy Miller as a vulgar and as free asthe representation of American culture that has correlated with the social life. On theother hand, the author describes Mrs. Costello as a Feudalistic of Europeanculture. Mrs. Costello is a representation as European social-life that alwaysdistinguishes between high and low status and it is one of the character of Feudalism.The feudalistic was that the power of the ruling class or Aristocracy rested on theircontrol of the farmable lands, leading to a class based upon the exploitation of thepeasants who farm these lands.